ChemInform Abstract: Recent Progress in Asymmetric Synthesis and Application of Difunctionalized Silicon‐Stereogenic Silanes. Issue 35 (August 2016) - Bauer, Jonathan O.; Strohmann, Carsten
Abstract: Review: 174 refs.